Analysis of TongueFit’s Usability Issues Using User Experience Method - Wardhani, Rizky Kusuma ; Wahyuni, Luh Karunia; Yusuf, Prasandhya Astagiri; Kekalih, Aria; Kusumaningsih, Widjajalaksmi (CV. Green Publisher Indonesia, 2025)
TongueFit designed to address the challenges of managing oral dysphagia in children. Integrating technology into rehabilitation has shown promise in enhancing therapeutic outcomes. Usability testing involving end-users is essential to ensure effectiveness and satisfaction. This research aims to evaluate usability issues of the prototype orofacial manometer, Tonguefit using user experience method. The assessment used a questionnaire modified from Baharum et al that was translated into Bahasa. To ensure face validity, the questionnaire was given to 3 users, who were required to evaluate the items with respect to ambiguity and understandability. Fleiss Kappa Index was used to determine the face validity. For user experience, 20 users who met the inclusion criteria were required. They were asked to assess the usability issue using the questionnaire. Data was transposed and analyzed using User Experience Questionnaire methodology. All reviewers of the instrument have had equal agreement and the questionnaire is clear and suitable to collect data (FKI 0.792). Based on the results of the user experience, the 2 variables obtained positive evaluation values, namely the Perceived Usefulness (mean 1.35) and Continuance Intention (mean 0.83). The highest evaluation value was on the Perceived Usefulness variable, while the lowest value was on the Interface Quality (mean 0.09). However, there is still potential for improvement to meet the desired standards of excellence. User feedback and suggestions have been instrumental in identifying areas for improvement. Tonguefit demonstrates strong perceived usefulness and continuance intention, while other areas require development to improve overall user satisfaction.